2015
DOI: 10.1590/1516-1439.270814
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Post-production Heat Treatment on Particleboard from Sugarcane Bagasse

Abstract: This study aimed to evaluate the effect of heat treatment on the physical and mechanical properties of particleboard from sugarcane bagasse. The experiment consisted of seven treatments arranged in a 2 × 3 factorial arrangement (two heat treatment times -8 and 12 min, and three heat treatment temperatures -200 °C, 230 °C, and 260 °C) and treatment control (without heat treatment). We evaluated the properties such as apparent density, water absorption after 2 and 24 h (WA2h andWA24h), thickness swell after 2 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 22 publications
1
11
0
2
Order By: Relevance
“…De acordo com Carvalho et al (2015) o tratamento térmico também pode ser uma alternativa no aprimoramento da estabilidade dimensional dos painéis produzidos, por reduzir a afinidade com água, uma vez que, visa degradar a hemicelulose e liberar a tensão de compressão formada durante a prensagem, porém o calor durante o processo pode promover a redução das propriedades mecânicas (Mendes et al, 2013).…”
Section: A B Cunclassified
“…De acordo com Carvalho et al (2015) o tratamento térmico também pode ser uma alternativa no aprimoramento da estabilidade dimensional dos painéis produzidos, por reduzir a afinidade com água, uma vez que, visa degradar a hemicelulose e liberar a tensão de compressão formada durante a prensagem, porém o calor durante o processo pode promover a redução das propriedades mecânicas (Mendes et al, 2013).…”
Section: A B Cunclassified
“…treatment on improving the dimensional stability. Carvalho et al, (2015) applied three thermal treatments (200, 230 and 260 °C) on particleboard produced from bagasse and found that water absorption in all the treatments varied significantly from the control. Del Menezzi, et al, 2009 reported that the post-heat treatment using two temperatures (190 and 220 °C) reduced the water absorption and thickness swelling of laboratory-produced oriented strand board.…”
Section: Resultsmentioning
confidence: 99%
“…O tratamento térmico é outra alternativa para aprimorar a estabilidade dimensional dos painéis produzidos e potencializar os resultados de desempenho físico por reduzir a afinidade com água, uma vez que visa degradar a hemicelulose e liberar a tensão de compressão formada durante a prensagem (CARVALHO et al, 2015).…”
Section: Resultsunclassified